Implications of The Integrated Administration Service (PATEN) Policy on Accountability and Public Satisfaction - Hayati, Rahmi; Jamiah (Socious Journal, 2025)
The implementation of the Integrated District Administrative Services (PATEN) represents a paradigmatic transformation in the provision of public services, emphasizing the integration of bureaucratic accountability and public satisfaction. This study aims to analyze the policy implications of PATEN on strengthening accountability mechanisms in public services and to examine its impact on the level of public satisfaction as service users. The research methodology employs a qualitative approach with a literature review technique, focusing on the analysis of academic literature and relevant policy documents published between 2021 and 2025. The analysis results show that the implementation of PATEN significantly contributes to strengthening accountability by increasing procedural transparency, standardizing services, and developing an integrated monitoring system. The positive impact on public satisfaction is reflected in increased service accessibility, staff responsiveness, and the simplification of previously complex bureaucratic processes. Furthermore, the determinant factors for the successful implementation of PATEN include the capacity and competence of human resources, the availability of technological infrastructure, leadership commitment, and the ability to adapt to local conditions and characteristics. Nevertheless, this study also identifies a number of challenges, including limited resources, resistance to change, and the digital divide between regions. Overall, the research concludes that PATEN has strategic potential as an instrument for bureaucratic reform capable of realizing good governance through public services that are of higher quality, accountable, and responsive to community needs.